Review: Depressive symptoms and fatigue as mediators of relationship between poor sleep factors and medication adherence in HIV-positive women. - Petrovic, Kimberly (Journal of Research in Nursing, 2015)
0 citations (Crossref) [2023-10-31] Place: (C)2015Sage Publications
Keywords: dept.nur

Dementia and Caregiver Stress: An Application of the Reconceptualized Uncertainty in Illness Theory. - Unson, Christine; Flynn, Deborah; Glendon, Mary Ann; Haymes, Elayne; Sancho, Diane (Issues in mental health nursing, 2015)
The Reconceptualized Uncertainty in Illness Theory (RUIT) was used to investigate antecedents to, appraisals of, and ways of coping with stressful caregiving. Four focus groups with caregivers (8 males and 16 females) of relatives with dementia were conducted; 15 cared for their parents and the remainder cared for their spouses. They were recruited from an adult care center and other community settings in a metropolitan area in New England. The discussions were audiotaped and transcribed verbatim. Two researchers independently coded the transcripts. Thematic analysis was structured according to the RUIT. The study is unique in its application to caregivers as opposed to patients and to all of the elements of the RUIT. Caregivers experience uncertainty in similar ways to patients with life-altering illness. Symptom severity–lack of personal boundaries, repetitive and aggressive behaviors, and the need for constant care–was the most frequent source of stress. The appraisals were mostly negative and included feelings of resentment, a lack of support from family members, financial strains, and loss of freedom. Self-improvement and self-care were important aspects of coping. Spirituality and humor were other coping skills that respondents used. Not all respondents said they were coping and some also reported that support from health care providers was not always helpful. Nurses can help improve coping by explaining the factors that contribute to caregiver strain and uncertainty, and by assisting caregivers to anticipate the effects of the caregiving role.
16 citations (Crossref) [2023-10-31] Place: England Unson, Christine. Southern Connecticut State University, Department of Public Health, New Haven, Connecticut, USA.
Keywords: *Adaptation; Psychological; *Caregivers/px [Psychology]; *Dementia/px [Psychology]; *Stress; Psychological/pc [Prevention & Control]; *Uncertainty; Adaptation; Psychological; Adult; Aged; Aged; 80 and over; Caregivers; Dementia; Dementia/th [Therapy]; Female; Humans; Male; Middle Aged; Models; Psychological; Narration; Stress; Psychological; Stress; Psychological/et [Etiology]; Uncertainty; adaptive behavior; adult; aged; caregiver; dementia; dept.nur; dept.pch; etiology; female; human; male; mental stress; middle aged; peer-reviewed; prevention and control; psychological model; psychology; uncertainty; verbal communication; very elderly